The Effect of the Webbed Learning Model on Learning Outcomes - Sandika, Rinaldy (Yayasan Sembilan Pemuda Indonesia, 2021)
The aim that the researcher wants to achieve is to see the effect of the webbed learning model on the learning outcomes of the V Thematic students of SDN 1 Mendo Barat. The population and sample of this study were all students of grade V SDN 1 Mendo Barat. This type of research is experimental research in the form of Non-equivalent Control Group Design. Data collection techniques are tests and documentation. Research data were analyzed using quantitative data analysis techniques. The posttest experiment calculation results obtained a mean of 78.610, while the posttest control calculation results increased in the acquisition of the mean of 73.540. In addition, this influence is also evidenced by the hypothesis test obtained by tobtained 2.345 greater than ttabel 1.714 so Ha is accepted and H0 is rejected. The results showed that the webbed learning model had an effect on the learning outcomes of fifth grade students in thematic subjects at SDN 1 Mendo Barat. A teacher must have creativity in the learning process, if a teacher has problems in student learning outcomes, researchers suggest the Webbed learning method because this method has been researched and student learning outcomes have developed from previous learning outcomes.